Effect Of Smartphone Dependency On Musculoskeletal System - Sapna Yadav; Dr. Nidhi Kalra (International Journal of Pharma and Bio Sciences, 2020)
Smartphone users are vulnerable to experience severe musculoskeletal pain due to the user’s static repeated motion, users minimal muscle tension caused by long hours of exposure, poor posture and using phone without breaks. Their constant repeated motion and posture during smartphone usage can lead to repetitive strain injury resulting in various symptoms like pain, discomfort or tingling, numbness in the upper extremities among which musculoskeletal pain is the most prominent symptom. To find the smartphone dependency among students and it effects on the musculoskeletal system a questionnaire based survey was done among 100 students. Musculoskeletal pain experienced by them was measured by Nordic musculoskeletal questionnaire. An informed consent was taken from students and they were asked to fill out the questionnaire. Data was analyzed and graphical represented by using Microsoft excel. There is a high prevalence of smartphone dependency among students as most of them agree that they feel anxiety when there is no phone around and it is also affecting their sleep and rest time. The students who are highly dependent on smartphones suffer from more musculoskeletal pain as compared to the students who are not dependent on smartphone and using it for lesser duration. Neck being the most affected region followed by upper back, wrists and shoulders. 54% students were suffering from neck pain, 42% students were suffering from upper back pain, 16% students were suffering from wrist pain and these are the students who spend more time on texting, 13% students were suffering from shoulder pain. Smartphone dependency is affecting student’s musculoskeletal system resulting in musculoskeletal pain.